2006
DOI: 10.1038/sj.emboj.7601078
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of actin dynamics by annexin 2

Abstract: Annexin 2 is a ubiquitous Ca 2 þ -binding protein that is essential for actin-dependent vesicle transport. Here, we show that in spontaneously motile cells annexin 2 is concentrated in dynamic actin-rich protrusions, and that depletion of annexin 2 using siRNA leads to the accumulation of stress fibres and loss of protrusive and retractile activity. Cells co-expressing annexin 2-CFP and actin-YFP exhibit Ca 2 þ -dependent fluorescense resonance energy transfer throughout the cytoplasm and in membrane ruffles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(186 citation statements)
references
References 45 publications
12
170
1
3
Order By: Relevance
“…A2IC plays an important role in the function of annexin A2 and contains an intracellular binding site for Ca 2+ , phospholipids and F-actin [12,20] . In the present work, we also found that the interaction between A2IC and actin is essential for maintaining the plasticity of the dynamic membrane-associated actin cytoskeleton [21] . The interaction of A2IC with other proteins could play a critical role in plasmindependent cell activation.…”
Section: Discussionsupporting
confidence: 75%
“…A2IC plays an important role in the function of annexin A2 and contains an intracellular binding site for Ca 2+ , phospholipids and F-actin [12,20] . In the present work, we also found that the interaction between A2IC and actin is essential for maintaining the plasticity of the dynamic membrane-associated actin cytoskeleton [21] . The interaction of A2IC with other proteins could play a critical role in plasmindependent cell activation.…”
Section: Discussionsupporting
confidence: 75%
“…For these experiments, confluent cultures were maintained at high density for 2 wk on glass coverslips before exposure to fluorescently labeled POS and subsequent fixation at defined time points. Cells were immunostained for anx A2 and also F-actin, because reorganization of the actin cytoskeleton is a key early event in phagocytosis, and in previous work we have shown that anx A2 is an important regulator of actin dynamics (Hayes et al, 2006). Confocal microscopy revealed enrichment of anx A2 and F-actin at the point of contact between POS aggregates and the apical RPE cell surface (arrowhead in Figure 2A).…”
Section: Anx A2 Is Recruited To the Forming Phagosomementioning
confidence: 78%
“…It has been proposed that phosphatidylinositol 4,5-bisphosphate (PtdIns4,5P 2 ) at the site of formation of the phagocytic cup and its subsequent hydrolysis as the cup closes are the key signaling events regulating the cycle of actin polymerization and depolymerization (Botelho et al, 2000;Scott et al, 2005). Because anx A2 is a potent regulator of actin dynamics (Merrifield et al, 2001;Hayes et al, 2006) and binds both cholesterol-rich membranes, Ca 2ϩ , and PtdIns4,5P 2 Rescher et al, 2004;Gerke et al, 2005), it is well placed to function as a sensor of these second messengers and signaling intermediates, linking . Tyrosine kinase signaling is defective in anx A2-deficient retinas.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, annexin A2 appears to be a necessary component of the machinery controlling endosomal membrane dynamics and multivesicular endosome biogenesis, and, in particular the clathrin-dependent endocytosis [71]. Annexin A2 also participates in the regulation of actin dynamics which is an important step in the endocytosis machinery [72]. ApoER2' may also facilitate endocytosis and signal transduction [73].…”
Section: Internalization and Apla Receptorsmentioning
confidence: 99%